Essays on Benjamin Britten from a centenary symposium - Forrest, David; Ankrum, Quinn Patrick; Jocoy, Stacey; Yates, Emily Ahrens (Cambridge Scholars Publishing, 2017)
Coming to terms with Britten's music is no easy task. The complex, often contradictory language associated with Britten's style likely stems from his double interest in progressive composition and immediate connection with a broad, popular audience - an apparent paradox in the splintered musical culture of the 20th century - as well as from complicated truths in his own life, such as his love for a country that accepted neither his sexuality nor his politics. As a result, the attempt to describe his music can tell us as much about our own biases and the inadequacies of our analytic tools as it.